Barriers that Prevent Teachers from Reporting Suspected Cases of Child ‎Maltreatment in Elementary‎ Schools at Mosul City /Iraq - Luay A. Al-Waly; Iqbal Ma'ala (Kufa Journal for Nursing Sciences)
Aim of the study: the study aim to identifying the barriers that prevent teachers of reporting suspected cases of child maltreatment in elementary schools at Mosul city.